2007
DOI: 10.1590/s1415-47572007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Extensive polymorphism and chromosomal characteristics of ribosomal DNA in the characid fish Triportheus venezuelensis (Characiformes, Characidae)

Abstract: The karyotype and chromosomal characteristics of the characid fish Triportheus venezuelensis were investigated using differential staining techniques (C-banding, Ag-NOR staining) and fluorescent in situ hybridization (FISH) with an 18S rDNA probe. The diploid chromosome number (2n = 52), karyotype composition and sex chromosome determination system of the ZZ/ZW type were the same as previously described in other species of the genus Triportheus. However, extensive variation regarding nucleolus organizer region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
2
26
0
5
Order By: Relevance
“…CF Yano et al Z chromosome was reported in T. venezuelensis and T. angulatus (Nirchio et al, 2007;Marquioni et al, 2013) that represent two of the most recently derived species, as their lineage originated at 5.2 ± 2.3 and 2.6 ± 1.4 Myr, respectively (Mariguela et al, 2016). Considering the fact that most species, including those originated from older Triportheus lineages, do not show an 18S rDNA cluster on the Z chromosome, it is more plausible to assume that these sequences were firstly translocated onto W and latter transposed from the W to the Z chromosome in T. venezuelensis and T. angulatus in independent events.…”
Section: Evolution Of Sex Chromosomes In Congeneric Speciesmentioning
confidence: 98%
See 2 more Smart Citations
“…CF Yano et al Z chromosome was reported in T. venezuelensis and T. angulatus (Nirchio et al, 2007;Marquioni et al, 2013) that represent two of the most recently derived species, as their lineage originated at 5.2 ± 2.3 and 2.6 ± 1.4 Myr, respectively (Mariguela et al, 2016). Considering the fact that most species, including those originated from older Triportheus lineages, do not show an 18S rDNA cluster on the Z chromosome, it is more plausible to assume that these sequences were firstly translocated onto W and latter transposed from the W to the Z chromosome in T. venezuelensis and T. angulatus in independent events.…”
Section: Evolution Of Sex Chromosomes In Congeneric Speciesmentioning
confidence: 98%
“…In fact, both techniques were critical to demonstrate the sequences that are still shared by both sex chromosomes or, otherwise, that those are more exclusive to one of them. Noteworthy, it was evidenced that the end of the Wq has a high concentration of female-specific sequences (Figures 2-4), where an 18S rDNA cluster is also located in all Triportheus species so far analyzed (Artoni and Evolution of sex chromosomes in congeneric species CF Yano et al Bertollo, 2002;Nirchio et al, 2007;Diniz et al, 2009;Marquioni et al, 2013;Yano et al, 2014). Sex chromosomes carrying 18S rDNA sequences have already been reported in several other vertebrates, such as Characidium fishes (Scacchetti et al, 2015), cane toad Bufo marinus (Abramyan et al, 2009), Chinese softshell turtle Pelodiscus sinensis (Kawai et al, 2007) and tiger snake Notechis scutatus (O'Meally et al, 2010).…”
Section: Chromosomal Rearrangements and Sex Chromosome Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies only refer to the diploid number, but have demonstrated karyotype variability, such as the occurrence of different cytotypes in the genus Bryconamericus (Paintner-Marques et al, 2002;Capistano et al, 2008), presence of B chromosomes in the genus Moenkhausia (Foresti et al, 1989;PortelaCastro et al, 2002), occurrence of sex chromosomes in the genus Triportheus (Nirchio et. al., 2007;Diniz et al, 2008), and different patterns of heterochromatin distribution in Oligosarcus (Rubert and Margarido, 2007;Hattori et al, 2007), among other examples.…”
Section: Introductionmentioning
confidence: 99%
“…Cistrons of ribosomal genes 5.8S, 18S, and 28S that form the nucleolar organizer regions in animals and are usually stained with silver nitrate (Ag-NORs), were observed in sex chromosomes, including insects as Drosophila (Pelegrini et al, 1977), beetles (Juan et al, 1993) and flies (Parise-Maltempi & Avancini, 2001); mammals (YonenagaYassuda et al, 1983;Oshida et al, 1999), and also plant chromosomes (Nakayama et al, 2001). Reports on the presence of Ag-NORs in fish sex chromosomes are restricted to Fundulus diaphanus (Howell & Black, 1979), Salvelinus alpinus (Reed & Phillips, 1997), Hoplias malabaricus (Born & Bertollo, 2000), Triportheus guentheri (Artoni & Bertollo, 2002), Triportheus venezuelensis (Nirchio et al, 2007) and Characidium lanei (Noleto et al, 2009). In the rainbow trout Oncorhynchus mykiss, which presents a sex determination system of the XX/XY type, the 5S ribosomal DNA was also observed on the X chromosome (Moran et al, 1996).…”
Section: Discussionmentioning
confidence: 99%